The epidemiology and virulence characteristics of Staphylococcus aureus isolates from bacteraemic patients at Tygerberg Hospital, South Africa - Van Rijswijk, Amike (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.